Biocatalysis and agricultural biotechnology (CRC Press, 2009)
Biocatalysis and Agricultural Biotechnology encapsulates the cutting-edge advances in the field with contributions from more than 50 international experts comprising sectors of academia, industry, and government research institutes, a virtual Who's Who among biocatalysis scientists.